Influence of Green transformational leadership on Green Innovation and Environmental Performance - Jamim, Asifa (My University, 2025)
The supervision of green transformational leadership is seen as a productive tool for developing green innovation and improving the environmental performance of an organisation. Green human resource management can serve as a mediating factor between green transformational leadership, green innovation, and environmental performance. This study examines the impact of green transformational leadership on green innovation and environmental performance through green human resource management. The research is undertaken in the ready-made garments industry in Bangladesh. A total of 200 managerial employees are conveniently selected from ready-made garments industry located in Dhaka, Savar, Gazipur, and Narayanganj cities of Bangladesh. A self-administered questionnaire is employed for data collection and analysed using the Statistical Package for the Social Sciences (SPSS) and Partial Least Squares Structural Equation Modelling (PLS-SEM). After ensuring convergent validity and discriminant validity of the constructs, the study hypotheses are tested through path coefficients. Green transformational leadership exerts a direct, positive, and significant impact on green innovation. Green human resource management is also positively and significantly influenced by green transformational leadership, serving as a mediating factor in the enhancement of green innovation and environmental performance within the ready-made garments industry. The study findings can help senior management, leaders, human resource specialists, garments industry experts, and decision-makers in understanding the need of developing a green culture to attain environmental sustainability goals.
Keywords: Green Transformational Leadership, Green Innovation, Environmental Performance, Green Human Resource Management, Ready-Made-Garments Industry, Partial Least Square Structural Equation Modelling (PLS-SEM).